Continuous-flow UV-C processing of kale juice for the inactivation of E. coli and assessment of quality parameters. (February 2021) - Pierscianowski, Jacob; Popović, Vladimir; Biancaniello, Michael; Bissonnette, Simon; Zhu, Yan; Koutchma, Tatiana
Graphical abstract: Highlights: Incident, average absorbed and delivered fluence values were reported. A 108.3 mJ cm −2 average absorbed fluence resulted in a 5.8 log E. coli reduction. Treatment had no effect on kale juice colour, chlorophyll or antioxidant content. Kale juice absorption coefficient decreased; sedimentation and browning increased. Abstract: Ultraviolet-C (UV-C) light is a non-thermal method for improving the safety and shelf-life of cold-pressed juices with minimal impact on quality and nutrition. Most previous studies have investigated fruit juices as opposed to particulate dense leafy green juices with very low UV transmittance (UVT). Pure kale juice is a common juice ingredient and represents the worst-case scenario in terms of low UVT green juices. This study validated the use of continuous benchtop UV-C treatment at 253.7 nm for 5-log reduction of non-pathogenic Escherichia coli P36 in kale juice. An average absorbed fluence of 108.3 mJ cm −2 resulted in a 5.8 log reduction of E. coli P36. At a fluence comparable to that reported for commercial juice processing (74.0 mJ cm −2 ), kale juice exhibited a decrease in absorption coefficient, while sedimentation, supernatant browning and pectin methylesterase activity increased with no effect on the chlorophyll content, colour, viscosity or antioxidant content.